2017
DOI: 10.1016/j.surg.2016.08.023
|View full text |Cite
|
Sign up to set email alerts
|

Early plasma transfusion is associated with improved survival after isolated traumatic brain injury in patients with multifocal intracranial hemorrhage

Abstract: Background Plasma-based resuscitation improves outcomes in trauma patients with hemorrhagic shock, while large animal and limited clinical data suggest that it also improves outcomes and is neuroprotective in the setting of combined hemorrhage and traumatic brain injury (TBI). However, the choice of initial resuscitation fluid including the role of plasma is unclear for patients after isolated TBI. Methods We reviewed adult trauma patients admitted from January 2011 to July 2015 with isolated TBI. “Early pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…17 A recent study has also demonstrated decreased mortality in traumatic brain injury (TBI) patients with multifocal hemorrhage that receive early administration of plasma. 18 …”
Section: Discussionmentioning
confidence: 99%
“…17 A recent study has also demonstrated decreased mortality in traumatic brain injury (TBI) patients with multifocal hemorrhage that receive early administration of plasma. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Whereas brain injury has been shown to cause altered vascular compensation in response to HS, 31 questions remain about the relationship between coagulopathy and the size of brain lesions. 15,22,30,32,33 Ratio-guided resuscitation with fresh frozen plasma (FFP) may have beneficial effects for patients with TBI + HS, 15 including fewer inflammatory complications. 5,6,9 In experimental large animal studies, early administration of FFP reduced the size of brain lesions, decreased cerebral edema, and substantially attenuated the degree of neurological impairment.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,9 However, very little is known about the clinical implications of DCR for patients with TBI and HS, especially considering the coagulopathy that often accompanies TBI. 1,1015 Additionally, there is virtually no data on how DCR affects neurologic status and outcomes with concomitant TBI.…”
Section: Introductionmentioning
confidence: 99%
“…It also incurs neuroprotection by providing higher brain oxygenation and cerebral perfusion profiles [30]. In humans, a large retrospective cohort analysis showed that in the subgroup of patients with multifocal intracranial hemorrhage, early administration of plasma was associated with a survival benefit [31].…”
Section: Benefits Of Early Plasma Transfusionmentioning
confidence: 99%